2013
DOI: 10.1016/j.jvs.2013.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of the angiosome model in peripheral vascular disease

Abstract: Vascular surgery has seen a revolutionary transformation in its approach to peripheral vascular disease over the last 2 decades, fueled by technological innovation and a willingness by the field to adopt these changes. However, the underlying pathology behind critical limb ischemia and the significant rate of unhealed wounds and secondary amputations despite apparently successful revascularization needs to be addressed. In seeking to improve outcomes, it may be beneficial to examine our approach to vascular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 43 publications
(54 reference statements)
0
72
0
1
Order By: Relevance
“…[74][75][76] Indeed, some evidence sug gests that wound healing and limb salvage is improved 64 with this method, especially for angioplasty, 75,76 although valid criticisms, such as the retrospective nature of these studies, have been raised. 77 A comparison of healing between surgical and endo vascular revascularization techniques revealed that for large wounds, surgical bypass seems to achieve better wound healing than endovascular techniques, in terms of the proportion of patients healed and with a trend for quicker healing. 78 Notably, in this group of patients, the presumption that bypass is dangerous while angioplasty is safe has been challenged by the authors of a review in which 30day mortality was 1.4% for bypass surgery, but mortality was still substantial at 0.5% after revasculari zation.…”
Section: Revascularizationmentioning
confidence: 99%
“…[74][75][76] Indeed, some evidence sug gests that wound healing and limb salvage is improved 64 with this method, especially for angioplasty, 75,76 although valid criticisms, such as the retrospective nature of these studies, have been raised. 77 A comparison of healing between surgical and endo vascular revascularization techniques revealed that for large wounds, surgical bypass seems to achieve better wound healing than endovascular techniques, in terms of the proportion of patients healed and with a trend for quicker healing. 78 Notably, in this group of patients, the presumption that bypass is dangerous while angioplasty is safe has been challenged by the authors of a review in which 30day mortality was 1.4% for bypass surgery, but mortality was still substantial at 0.5% after revasculari zation.…”
Section: Revascularizationmentioning
confidence: 99%
“…Since Attinger et al advocated the importance of the angiosome concept in lower limb revascularization, 44 the clinical significance has been widely debated ( Table 2). 45 As reported by Alexandrescu et al in their study titled "Angiosome concept: fact or fiction? ", some reports state that the angiosome concept is very useful clinically, while others state that the angiosome concept, though important as a concept, is not of any particular importance clinically.…”
Section: Impact Of Pedal Arch Quality and The Arterial-arterial Connementioning
confidence: 96%
“…There are reports of attempts to evaluate the arterial-arterial connection between angiosomes using local hemodynamic parameters and new imaging methods, as discussed later. 45,[58][59][60][61] Connections between angiosomes and the development of collateral pathways will differ according to the background disease and state of infection. Microcirculatory disorder is often serious in long-term diabetes patients and dialysis patients.…”
Section: Impact Of Pedal Arch Quality and The Arterial-arterial Connementioning
confidence: 99%
“…Recently, this concept has been used widely for the purpose of foot revascularization in patients with critical limb ischemia (CLI). 1,2 The key benefit of the angiosome-based approach is that it divides areas of ischemic tissue loss into angiosomes and selects the angiosome-matched vessels for revascularization. 3 This could potentially provide optimal conditions for wound healing and limb salvage.…”
mentioning
confidence: 99%
“…The plantar heel is also supplied by the medial calcaneal branches of PTA. Reproduced from the figure in previously published article by Sumpio et al1 …”
mentioning
confidence: 99%